Peningkatan Pengetahuan, Sikap dan Perilaku Perawat Melalui Pelatihan Kredensial Profesi Keperawatan (Journal of Telenursing (JOTING), 2021)
This study aims to determine the effect of nursing profession credential training on increasing nurses' knowledge, attitudes, and behavior in the surgical ward of the Aceh Government General Hospital. The method used is a quasi-experimental design with a non-control group pretest-posttest. The number of samples was 46 respondents who were selected through the total sampling method. The results showed that there was an effect of nursing profession credential training on increasing knowledge (p-value 0.0001), attitude (p-value 0.0001) and behavior (p-value 0.0001) of nurses in the operating room of the Aceh Hospital. In conclusion, nursing profession credential training can improve nurses' knowledge, attitudes, and behavior in the surgical ward of the Aceh Government General Hospital.Keywords: Credentials, Training, Nurses, Knowledge, Behavior, Attitude